Lifestyle factors modulate postprandial hypertriglyceridemia: From the CORDIOPREV study. (November 2019) - Leon-Acuña, Ana; Torres-Peña, Jose D.; Alcala-Diaz, Juan F.; Vals-Delgado, Cristina; Roncero-Ramos, Irene; Yubero-Serrano, Elena; Tinahones, Francisco J.; Castro-Clerico, Manuel; Delgado-Lista, Javier; Ordovas, Jose M.; Lopez-Miranda, Jose; Perez-Martinez, Pablo
Abstract: Background and aims: Recent evidence suggests that postprandial hypertriglyceridemia (PPT) is associated with the incidence of CVD. Several non-modifiable factors (genetics, age, gender) and lifestyle factors (physical activity, smoking, regular alcohol) have shown their ability to modulate PPT. We evaluate the influence of regular alcohol intake, physical activity and smoking habit modulating PPT in the CORDIOPREV study (NCT00924937). Methods: 1002 patients were subject to an oral fat load test meal and serial blood samples were drawn at 0, 1, 2, 3 and 4 h during postprandial state. A PPT concentration above 2.5 mmol/L (220 mg/dL) at any time point has been established as a detrimental response. Alcohol consumption was defined as non-drinkers, moderate and severe intake; regular physical activity exceeding than or lower than 1000 MET/week; smoking habit was classified in current, never, recent ex-smokers and long-term ex-smokers. Results: The prevalence of undesirable PPT response was 68% in current, 58% in recent ex-smokers, 49% in long-term ex-smokers and 48% in never smokers ( p  < 0.001). Current and recent ex-smokers displayed higher PPT response as well as a greater area under the curve (AUC) and higher incremental (iAUC) of triglycerides (TG) compared with long-term ex-smokers and never smokers ( p  < 0.05), without differences among these subgroups. No differences were observed in the magnitude of PPT according to regular physical activity or alcohol intake habits. Conclusions: Smoking is an independent risk factor modulating the magnitude of PPT. However, after tobacco cessation, ex-smokers show a progressive decrease on their PPT to reach levels similar to those of never smokers. Graphical abstract: Image 1 Highlights: We studied the influence of regular alcohol intake, physical activity and smoking habit modulating PPT in the CORDIOPREV study. PPT and the prevalence of undesirable response was evaluate in each subgroups. We assessed the main determinants risk factors in the presence of undesirable response. Smoking is an independent risk factor modulating the magnitude of PPT. After tobacco cessation, in long-term ex-smokers, PPT progressively decreases to similar magnitude to never smokers. No differences observed in the magnitude of PPT according to regular physical activity or alcohol intake habits.